2007
DOI: 10.1142/s0129183107011297
|View full text |Cite
|
Sign up to set email alerts
|

Majority-Vote on Directed Small-World Networks

Abstract: On directed Small-World networks the Majority-vote model with noise is now studied through Monte Carlo simulations. In this model, the orderdisorder phase transition of the order parameter is well defined in this system. We calculate the value of the critical noise parameter q c for several values of rewiring probability p of the directed Small-World network. The critical exponentes β/ν, γ/ν and 1/ν were calculated for several values of p.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 20 publications
3
37
0
Order By: Relevance
“…Studies on regular lattices showed the critical exponents are the same as those of the Ising model [3][4][5][6][7], in accordance with the conjecture by Grinstein et al [8]. The MV2 model has also been extensively studied in complex networks, including random graphs [9,10], small world networks [11][12][13], scale-free networks [14][15][16], and some others [17,18].…”
Section: Introductionsupporting
confidence: 57%
“…Studies on regular lattices showed the critical exponents are the same as those of the Ising model [3][4][5][6][7], in accordance with the conjecture by Grinstein et al [8]. The MV2 model has also been extensively studied in complex networks, including random graphs [9,10], small world networks [11][12][13], scale-free networks [14][15][16], and some others [17,18].…”
Section: Introductionsupporting
confidence: 57%
“…On complex networks, the MVM shows different behavior [16][17][18][19][20][21][22][23]. Campos et al investigated MVM on undirected small-world networks [16] and found the critical exponent ratios γ/ν and β/ν to differ from those of the Ising model [14]; they depend on the rewiring probability.…”
Section: Introductionmentioning
confidence: 99%
“…Campos et al investigated MVM on undirected small-world networks [16] and found the critical exponent ratios γ/ν and β/ν to differ from those of the Ising model [14]; they depend on the rewiring probability. Luz and Lima studied the MVM on a directed small-world network [17] (see Sánchez et al [24] for its construction). Their critical exponent ratios γ/ν and β/ν also are different from those of the Ising model on square lattices and in this case the MVM exponents do not depend on the rewiring probability, in contrast to results of Campos et al [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the order to achieve his goal he used 44 (LS) Archimedean lattice. However, also with the aim of improve this criterion other researchers studied MVM on several other topologies that are not Archimedeans [39,[43][44][45][46][47][48]. To their surprise all results obtained for the critical exponents are different from results obtained by M. J. Oliveira, and are also different for each topology used.…”
Section: Introductionmentioning
confidence: 99%